1996
DOI: 10.1046/j.1365-2788.1996.792792.x
|View full text |Cite
|
Sign up to set email alerts
|

Respondent and informant accounts of psychiatric symptoms in a sample of patients with learning disability

Abstract: This paper investigates differences in the nature and frequency of psychiatric symptoms reported by patients with learning disability and key informants. The study involved psychiatric assessment of 100 patients with learning disabilities and key informants using the Psychiatric Assessment Schedule for Adults with a Developmental Disability (PAS-ADD), a semi-structured psychiatric interview developed specifically for people who have a learning disability. There was considerable disagreement between respondent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…The 1993 study reported good reliability on informantreport (mean kappa for all items = .72). However, in a second study, Moss, Prosser, Ibbotson, and Goldberg (1996) reported poor inter-rater reliability for respondent and informant versions of the scale (i.e., in only 40% of cases did both versions yield a diagnosis). These data are consistent with published informant and self-report data on the PIMRA from over a decade earlier in that self-report when compared to informant data was generally a more accurate rating method (Matson et al, 1984).…”
Section: Psychiatric Assessment Schedule For Adults With Developmentamentioning
confidence: 88%
“…The 1993 study reported good reliability on informantreport (mean kappa for all items = .72). However, in a second study, Moss, Prosser, Ibbotson, and Goldberg (1996) reported poor inter-rater reliability for respondent and informant versions of the scale (i.e., in only 40% of cases did both versions yield a diagnosis). These data are consistent with published informant and self-report data on the PIMRA from over a decade earlier in that self-report when compared to informant data was generally a more accurate rating method (Matson et al, 1984).…”
Section: Psychiatric Assessment Schedule For Adults With Developmentamentioning
confidence: 88%
“…In contrast, the core symptoms of psychosis, hallucinations and delusions, are highly abstract, and cannot be inferred from external behaviour with any degree of certainty. Moss et al (1996b) found the only first-rank symptom which could be detected with any frequency in their verbally competent sample was auditory hallucinations. Almost none of the respondents or informants was able to give an account of thought disorder or passivity delusions which was sufficiently unequivocal to fulfill the SCAN algorithm.…”
Section: Rationale and Conceptual Evolution Of The Pas-add Systemmentioning
confidence: 90%
“…Important findings were made at this time about schizophrenia and its probable over-diagnosis (Moss et al, 1996a), and about the relationships between patient and informant accounts (Moss et al, 1996b). Overall, it became clear how useful it is to get a patient account, and how difficult it can be to get one.…”
Section: Pas-add 10: the First Of The Assessmentsmentioning
confidence: 98%
“…Clinical interviewing is of limited usefulness, so assessment must rely heavily on information from caregivers, and treatment records, as well as observation. Diagnosis in the absence of a full verbal account by the patient does, however, pose validity problems (Moss et al, 1996b). To maximize diagnostic validity, multiple perspectives on the individual's behavior must be coupled with carefully structured methods for recording symptoms, encompassing all the variables that influence an individual's behavior (e.g., biomedical, psychological, interactional, environmental) (Gardner and Sovner, 1994;Griffiths, 1995;Moss and Lee, 2001).…”
Section: Diagnostic Issuesmentioning
confidence: 99%